Does the nutritional condition limit survival potential of sardine Sardina pilchardus (Walbaum, 1792) larvae off the north coast of Spain? RNA/DNA ratios and their variability - Chicharo, Maria Alexandra (2013)
The aim of this study was to determine the nutritional condition of Sardina pilchardus larvae and the percentage of larvae that were starving at the time of capture. The survey was conducted, during the spawning season, in April and May of 1991 and 1992, off the northern coast of Spain. An accepted ¯uorimetric technique was used to determine the concentrations of both RNA and DNA and to calculate RNA/DNA ratio for each larva. RNA/DNA ratios were related to the zooplankton biomass (>53 mm). Low percentages of starving larvae (RNA/DNA ratio less than 1.3) were registered, ranging from 0% to 2.5%. Results based on the mean and variance of individual larval growth rates showed that predation pressure was not increasing from 1991 to 1992. Based on the presence of sardine larvae in good condition together with low predation, a high recruitment was expected. However, the 1993 recruitment, from 1992 spring spawning, was very poor. This was associated mainly with unfavourable advection from the nursery area. Moreover, even low levels of starvation, such as registered, operating over long time periods could have considerable consequences for larval mortality.